"Influenza" versus "Flu": Do Different Medical Terms Affect Vaccination Intention?. Issue 4 (3rd April 2019) - Cummings, Christopher L.; Kong, Wei Yi
Abstract : Confusion about disease terminology contributes to lower risk perceptions that may lead to lesser engagement in protective measures. Communication campaigns promoting influenza vaccination have become commonplace around the world. Such campaigns vary widely in their terminology used from depicting the disease and response formally as an "influenza vaccination" to more colloquial terms like "flu shot." This study gathered responses from 896 Singapore residents through an online experiment and employed a Chi-square test to assess if different medical terms describing the same preventive measure ("influenza vaccine" and "flu shot") influence vaccination intentions. Results indicate that the formal term "influenza vaccine" prompts significantly greater vaccination intention than the abbreviated colloquial term "flu shot, " even when no further information about the disease or vaccine is provided. This finding suggests that the proclivity to use the less formal term "flu shot" in widespread campaigns is less advantageous in prompting intentions to vaccinate against the disease. This may be the result of an activated availability bias brought on by the distinct semantic frames. We conclude that in this instance the medical terms should not be used interchangeably and that "influenza vaccine" may be more advantageous in future communication to encourage adoption of advised health behavior.